TINDAK TUTUR ILOKUSI PADA PROGRAM ACARA SAPA KALBAR DI KOMPAS TV PONTIANAK - Wulandari, Tika; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractResearch on illocutionary speech acts in the Sapa Kalbar program on Kompas TV Pontianak was conducted on aspects of assertive speech acts, directive speech acts, commission speech acts, expressive speech acts, and declarative speech acts. The purpose of this study was to describe the illocutionary speech acts in the Sapa Kalbar program on Kompas TV Pontianak and the implementation of Indonesian language learning in schools. This research is in the form of qualitative with descriptive method. The data in this study were sourced from the Sapa Kalbar program. The data collection technique used is the documentary technique. The tools used are laptops and gadgets. The results showed that the illocutionary speech acts in the Sapa Kalbar program on Kompas TV Pontianak were 77 utterances consisting of 59 assertive speech acts, 9 directive speech acts, 1 commissive speech act, 5 expressive speech acts, and 3 declarative speech acts. speech. Then, this research has a relationship with Indonesian language lessons in class VIII odd semesters with news text material that refers to Basic Competencies 3.1 and 4.1.Keywords: Speech Acts, Illocutionary, Event Program